PENGARUH PENGAWASAN, SISTEM AKUNTANSI DAN PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH - Sitti Murniati (AkMen JURNAL ILMIAH, 2020)
Local government performance is a description of the level of achievement of the implementation of an activity/program/policy in realizing the goals, objectives, mission and vision of the organization as stated in the formulation of an organization's strategic planning. Therefore, the measurement of local government performance must include financial and non-financial performance measurement. Measurement of local government performance is directed at each organization that has been given the authority to manage resources in accordance with their respective fields. The research objective was to determine and analyze the effect of supervision, accounting systems and regional financial management on local government performance, either partially or simultaneously. The research sample came from 60 local government employees and the method of analysis used was multiple regression analysis with the IBM SPSS Statistics program. The results showed that supervision, accounting systems and regional financial management had a positive and significant effect on local government performance, either partially or simultaneously and supervision was the most dominant variable affecting local government performance